Emergence of Multidrug-Resistant Influenza A(H1N1)pdm09 Virus Variants in an Immunocompromised Child Treated With Oseltamivir and Zanamivir. (5th May 2015) - Tamura, Daisuke; DeBiasi, Roberta L.; Okomo-Adhiambo, Margaret; Mishin, Vasiliy P.; Campbell, Angela P.; Loechelt, Brett; Wiedermann, Bernhard L.; Fry, Alicia M.; Gubareva, Larisa V.
Abstract: Prolonged treatment of an immunocompromised child with oseltamivir and zanamivir for A(H1N1)pdm09 virus infection led to the emergence of viruses carrying H275Y and/or E119G in the neuraminidase (NA). When phenotypically evaluated by NA inhibition, the dual H275Y-E119G substitution caused highly reduced inhibition by 4 NA inhibitors: oseltamivir, zanamivir, peramivir, and laninamivir.